A COMPARATIVE STUDY OF JUDICIAL RESTRAINT AND ACTIVISM ON THE MATERIAL REVIEW OF PRESIDENTIAL THRESHOLD IN THE CONSTITUTIONAL COURT - NAHDLIYAH, HADZIQOTUN; SASTRADINATA, DHEVINAYASARI; WINARNO, JATMIKO; TJAHJANI, JOEJOEN; YANTO, M. (Jurnal Independent, 2023)
Abstract The doctrine of Judicial Restraint and Judicial Activism has become a debate in democraticcountriesondecisionsrelatedtothepresidentialnominationthreshold (presidential threshold) made by the Constitutional Court. In the application of judicial restraint, judges are more self-limiting in deciding a case and are more restrained in their authority, in contrast to judicial activism which is more active and brave in providing new legal breakthroughs on the norms being tested. In this paper, the formulation of the problem to be discussed is How the Decision of the Constitutional Court Judges Applying the Doctrine of Judicial Restraint Against the Presidential Threshold Lawsuit in the Presidential Election and the Development of Democracy in Indonesia and How the Relationship between the Decision of the Constitutional Court Judges Using the Doctrine of Judicial Activism Against the Presidential Threshold Lawsuit in the Presidential Election and the Development of Democracy in Indonesia. This paper also uses normative legal research methods, which is a process to analyze legal rules, legal principles and legal doctrines. The problem approach in this writing is the statute approach and conceptual approach.